Penyuluhan kesehatan tentang pengaruh air bersih dan sanitasi terhadap masalah kesehatan (stunting) - Eka Yudha Chrisanto; Riska Wandini; Vera Yulyani; Nirwanto Nirwanto; Mardani Mardani; Mega Dewi Anggraini; Utari Aditia Selvianti (JOURNAL OF Public Health Concerns, 2023)
Background: Stunting is a condition where toddlers have a length or height that is less than their age. From the results of the preliminary study at the Panjang Health Center in Bandar Lampung City, it was found that 39.95% of children experienced stunting problems. Children who experienced stunting problems in the Kelurahan Panjang Selatan neighborhood I and II can be caused by several factors such as environmental sanitation, food and beverage processing and mother’s knowledge of stunting. This needs further follow-up. Purpose: Respondents can find out about the influence of access to water and sanitation on health problems (Stunting). Methods: The implementation of the method used in community service is carried out in 2 stages, firstly, students of the Nursing Science Study Program (PSIK) explain the effect of water clean and sanitation on health problems (Stunting) using leaflets and secondly, after being given counseling about the effect of water clean and sanitation to health problems (Stunting), respondents were given questions and answers about the affect of clean water and sanitation on health problems (Stunting). Results: Respondents understand about the effect of clean water and sanitation on health problems (Stunting). Conclusion: Respondents can do their own way to prevent and reduce the risk of stunting in children, one of which is by implementing clean water treatment and improving adequate and good sanitation facilities. Keywords: Health Education; Effect of Clean Water; Sanitation; Stunting. Pendahuluan: Stunting merupakan suatu kondisi dimana balita memiliki panjang atau tinggi badan yang kurang jika dibandingkan dengan umurnya. Dari hasil prevalensi di Puskesmas Panjang Kota Bandar Lampung di dapat data sebesar 39,95% anak mengalami masalah stunting.Anak yang mengalami masalah stunting di wilayah Kelurahan Panjang Selatan Lingkungan I dan II dapat disebabkan oleh beberapa faktor seperti sanitasi lingkungan, pengolahan makanan dan minuman serta pengetahuan ibu terhadap stunting. Hal tersebut tentunya perlu ditindak lanjut lagi. Tujuan: Responden dapat mengetahui, memahami terkait pengaruh air bersih dan sanitasi terhdap masalah kesehatan (Stunting) pada anak. Metode: Pelaksanaan metode yang digunakan dalam pengabdian masyarakat ini dilakukan dengan 2 tahap yaitu pertama mahasiswa Program Studi Ilmu Keperawatan (PSIK) menjelaskan tentang pengaruh dari air bersih dan sanitasi terhadap masalah kesehatan (Stunting) menggunakan lembar leaflet dan ke dua setelah diberikan penyuluhan tentang pengaruh air bersih dan sanitasi terhadap masalah kesehatan (Stunting), responden diberikan Tanya jawab tentang pengaruh air bersih dan sanitasi terhadap masalah kesehatan (Stunting). Hasil: Responden memahami tentang pengaruh air bersih dan sanitasi terhadap masalah kesehatan (Stunting). Simpulan: Responden dapat melakukan sendiri cara untuk mecegah dan mengurangi resiko terjadninya stunting pada anak salah satunya dengan pengolahan air bersih dan perbaikan fasilitas sanitasi yang memadai serta baik untuk diterapkan.